The use of imagery to manipulate challenge and threat appraisal states in athletes - Williams, S. E.; Cumming, J.; Balanos, G. M. (Journal of Sport & Exercise Psychology, 2010)
The present study investigated whether imagery could manipulate athletes` appraisal of stress-evoking situations (i.e., challenge or threat) and whether psychological and cardiovascular responses and interpretations varied according to cognitive appraisal of three imagery scripts: challenge, neutral, and threat. Twenty athletes (Mage = 20.85; SD = 1.76; 10 female, 10 male) imaged each script while heart rate, stroke volume, and cardiac output were obtained using Doppler echocardiography. State anxiety and self-confidence were assessed following each script using the Immediate Anxiety Measures Scale. During the imagery, a significant increase in heart rate, stroke volume, and cardiac output occurred for the challenge and threat scripts (p < .05). Although there were no differences in physiological response intensities for both stress-evoking scripts, these responses, along with anxiety symptoms, were interpreted as facilitative during the challenge script and debilitative during the threat script. Results support using imagery to facilitate adaptive stress appraisal.